Baby swimming and respiratory health - Nystad, Wenche (2008)
AIM: To estimate the effect of baby swimming the first six months of life on respiratory diseases from 6 to 18 months. METHODS: We used data from The Norwegian Mother and Child Cohort Study (MoBa) conducted by the Norwegian Institute of Public Health in children born 1999 – 2005 followed from birth to the age of 18 months (n = 30,870). Health outcomes: lower respiratory tract infections (LRTI), wheeze and otitis media between 6 and 18 months of age. Exposure: baby swimming at age 6 months. The effect of baby swimming was estimated by logistic regression analysis adjusting for potential confounders. RESULTS: About 25% of the children participated in baby swimming. The prevalence of LRTI was 13.3%, wheeze 40.0% and otitis media 30.4%. Children who were baby swimming were not more likely to have LRTI, to wheeze or to have otitis media. However, children with atopic mothers who attended baby swimming had an increased risk of wheeze, aOR 1.24 (95% CI 1.11, 1.39), but not LRTI or otitis media. This was also the case for children without respiratory diseases before 6 months aOR 1.08 (95%CI 1.02–1.15). CONCLUSION: Baby swimming may be related to later wheeze. However, these findings warrant further investigation.